Electronic business interoperability : concepts, opportunities and challenges - Kajan, Ejub, 1953- (Hershey, PA : Business Science Reference, 2011)
'This book analyzes obstacles, provides critical assessment of existing approaches, and reviews recent research efforts to overcome interoperability problems in electronic business'--Provided by publisher.
E-business interoperability : a systematization attempt based on the morphology concept / Frank-Dietter Dorloff, Veith Jahns, Volker Schmitz -- Business artifacts for e-business interoperability / Yoakim Badr, Nanjangud C. Narendra, Zakaria Maamar -- A semantic similarity analysis for data mappings between heterogeneous xml schemas / Jaewook Kim, Yun Peng -- Putting interoperability on the map : towards a framework of interoperability approaches and tools / Stelios Eliakis, Eleni Zampou, Katerina Pramatari -- Process mediation : requirements, experiences and challenges / Roman Vaculin, Roman Neruda, Katya Sycara -- Verification of e-commerce business processes / Sven Feja ... [et al.] -- Validating component-based implementations of business processes / Jens Lemcke, Andreas Friesen, Tirdad Rahmani -- E-business interoperability and collaboration / Alexander Kipp, Lutz Schubert -- Requirements metadata driven dynamic configuration of business processes / Marcus Spies, Azzelarabe Taleb-Bendiab -- Planning based service composition / Maja Vukovic, Peter Robinson -- Semantic technologies and e-business / Ivan Bedini, Georges Gardarin, Benjamin Nguyen -- Context-sensitive ontology matching in electronic business / Jingshan Huang, Jiangbo Dang -- Approaches for evaluating the conformance and interoperability of ontology engineering tools / Ra Garcia Castro, Asunci Gez-Pez -- Semantic interoperability enablement in e-business modeling / Janina Fengel -- Development of an ontology-based e-recruitment application that integrates social web / Michel Treault, Aude Dufresne, Michel Gagnon -- Trade collaboration systems / Peter Denno -- The semantic web as a catalyst for enterprise/industrial interoperability / Atanasios P. Kalogeras, Christos Alexakos, Manis Georgoudakis -- ebXML-based electronic business interoperability framework and test platform / Peng Liang ... [et al.] -- An ontology-based framework to semantically describe XML-based business documents / Mariela Rico ... [et al.] -- Business document exchange between small companies / Flavio Bonfatti, Paola Daniela Monari, Luca Martinelli -- Interoperability in the building of next generation of collaborative working environments / M. Antonia Martinez-Carreras, Antonio Ruiz-Martinez, Manuel Bernal Llinares -- HLA supported, federation oriented enterprise interoperability / Gregory Zacharewicz, David Chen, Bruno Vallespir -- Convergence of information security in B2B networks / Dan Harnesk -- E-business and information security risk management : challenges and potential solutions / Stefan Fenz -- On interoperability failures in WS-security : the XML signature wrapping attack / Nils Gruschka ... [et al.] -- Interoperability in identity management / Martin Wolf.
Includes bibliographical references and index.
Keywords: Electronic commerce; Internetworking (Telecommunication); Electronic commerce -- Computer programs